2020
DOI: 10.1038/s12276-020-00543-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of thrombus, gut, and oral microbiomes in Korean patients with ST-elevation myocardial infarction: a case–control study

Abstract: ST-segment elevation myocardial infarction (STEMI) is characterized by thrombotic coronary artery occlusions caused by atherosclerotic plaque rupture. The gut microbiome potentially contributes to the pathogenesis of coronary artery diseases. This study investigated the microbial diversity and composition of coronary thrombi in STEMI patients and the composition of the thrombus microbiome relative to that of the oral and gut microbiomes. A case–control study was performed with 22 STEMI patients and 20 age- and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 47 publications
0
24
0
Order By: Relevance
“…A similar result was found by Kamo et al ( 2017 ) regarding the gut microbiota in heart failure patients and HC subjects (Mayerhofer et al, 2020 ). The beta diversity values of the gut, oral, and thrombus microbiomes were found to be significantly different in Korean patients with ST-elevation myocardial infarction (Kwun et al, 2020 ). Particularly, the results of this study revealed partial separation between both groups.…”
Section: Discussionmentioning
confidence: 99%
“…A similar result was found by Kamo et al ( 2017 ) regarding the gut microbiota in heart failure patients and HC subjects (Mayerhofer et al, 2020 ). The beta diversity values of the gut, oral, and thrombus microbiomes were found to be significantly different in Korean patients with ST-elevation myocardial infarction (Kwun et al, 2020 ). Particularly, the results of this study revealed partial separation between both groups.…”
Section: Discussionmentioning
confidence: 99%
“…Proteobacteria are seen to increase in the faecal microbiota of patients with ST‐segment elevation myocardial infarction (STEMI) 30 . Desulfovibrionaceae belonged to the phylum Proteobacteria (Delta) 31 .…”
Section: Discussionmentioning
confidence: 99%
“…**p ≤ 0.01, ***p ≤ 0.001, ****p ≤ 0.0001, for MI + DAPA vs MI group. ## p ≤ 0.01, #### p ≤ 0.0001, for Sham vs MI group Proteobacteria are seen to increase in the faecal microbiota of patients with ST-segment elevation myocardial infarction (STEMI) 30.…”
mentioning
confidence: 98%
“…In MI patients, microorganisms belonging to the oral microbiota, such as Lactobacillus, Bacteroidetes , and Streptococcus , have been isolated from the bloodstream. Likewise, a high proportion of the phyla Proteobacteria and Bacteroidetes is found in thrombus samples ( Zhou et al., 2018 ; Koren et al., 2011 ; Kwun et al., 2020 ). Increasing studies evaluated the interplay between the microbiota of the oral cavity and the intestine.…”
Section: Introductionmentioning
confidence: 99%
“…In one study, the genera Veillonella and Streptococcus were identified in samples analyzed from three different niches, oral cavity, intestine, and atherosclerotic plaque from the same patient ( Koren et al, 2011 ). Likewise, in STEMI patients, alterations of the gut microbiota (GM) have been described, characterized by an increase in Bacteroides and Prevotella , as well as changes related to a greater GM diversity associated with clinical characteristics of poor oral health ( Kwun et al., 2020 ; Xu et al., 2021 ; Yin et al., 2015 ; Gao et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%